Biochemical and phytochemical evaluation of Stevia rebaudiana - Howlader, Md Moniruzzaman Sohag; Ahmed, Sheikh Rashel; Kubra, Khadizatul; Bhuiyan, Md Khairul Hassan (Asian Journal of Medical and Biological Research, 2016)
<!–[if gte mso 9]> ismail - [2010] 11.5606 <![endif]–> The present study was aimed to evaluate biochemical and phytotochemical of dry leaves of Stevia rebaudiana. Biochemical analysis indicated that Stevia leaves are a good source of carbohydrate and reducing sugar. Different extraction methods were used to prepare four different dry extracts (Extract A, B, C, D). Total soluble sugars and reducing sugars were analyzed for these four dry extracts and commercial Stevia powder. The highest amount of total soluble sugar (477 mg sugar g-1 dry extract) was obtained from extract C and higher amount of reducing sugar (82 mg g-1 dry extract) was obtained from extract D among the extracts. But commercial Stevia powder showed higher total soluble sugar content (754 mg g-1 dry powder) and highest amount of reducing sugar (98 mg g-1 dry extract) than all the extracted dry samples. The extraction process of dry extract C was feasible for the extraction of total soluble sugar. For the phytochemical screening, crude extract was tested for the presence of different chemical groups and presence of alkaloids, phenolic compounds, steroids, tannins, flavonoids, cardiac glycosides and saponins that were identified. The highest amount of total phenolic compounds (92 mg) was recorded from methanolic extract of extraction B. The lowest amount of total phenolic compounds (36 mg) was recorded in ethanolic extract of extraction A. So, Methanol proved as best solvent to extract increased quantity of total phenolic compounds than other solvents. Asian J. Med. Biol. Res. March 2016, 2(1): 121-130 <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>